PENGARUH KARAKTERISTIK YOUTUBE VLOGGER TERHADAP PARASOCIAL INTERACTION DAN PURCHASE INTENTION DARI VIEWERS VLOG TITAN TYRA - Shelly Antoinette (Jurnal Strategi Pemasaran, 2019)
This study examines the effect of YouTube Vlogger characteristics on Parasocial Interaction and Purchase Intention. A conclusive research design follows the examination through literature review to generate hypotheses and the design of purposive sampling given the applied research. A Googlebased online survey was deployed, generating a usable 104 respondents who had had seen the review video from Titan Tyra, a YouTube vlogger. Results from the Partial Least Square structural equation modelling analyses showed substantial empirical evidence that supported all research hypotheses.